Degradable self-healing protective coating based on nanotechnology and preparation method thereof

Through the synergistic effect of modified polyurethane and modified nanotitanium dioxide, the problem of insufficient self-healing and degradability of polyurethane is solved, the ultraviolet resistance and dispersion of the coating are improved, and high-performance degradable self-healing protective coating is achieved.

CN119899581AInactive Publication Date: 2025-04-29REDHOT (HAINAN) ENTERPRISE MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077304.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among the existing degradable self-healing protective coatings, the self-healing and degradability of polyurethane are insufficient, and the dispersibility of nanofillers are poor, which affects the overall performance of the coating.

Method used

Modified polyurethane is used as the main body of the coating, and modified nanotitanium dioxide, curing agent, leveling agent and mixed solvent are added. Through the preparation method of modified polyurethane and the doping of nanotitanium dioxide, the coating is improved to improve the UV resistance, degradability, self-healing and protective properties.

Benefits of technology

The coating has achieved good UV resistance, degradability, self-healing and protective properties, improved the degradability and thermal stability of polyurethane, and improved the dispersion of nanotitanium dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247477410000081
    Figure BDA0005247477410000081
  • Figure BDA0005247477410000091
    Figure BDA0005247477410000091
Patent Text Reader

Abstract

The invention relates to the field of coatings, and provides a degradable self-healing protective coating based on nanotechnology and a preparation method thereof, the coating comprises the following raw materials by weight: 65-80 parts of modified polyurethane, 5-15 parts of modified nano titanium dioxide, 10-20 parts of a curing agent, 1-2 parts of a leveling agent, and 10-20 parts of a mixed solvent. The coating provided by the invention has the characteristics of good ultraviolet resistance, degradability, self-healing performance and protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a degradable self-healing protective coating based on nanotechnology and a preparation method thereof. Background Art

[0002] With the development of the economy, especially the rapid development of the construction industry, automobile industry, and transportation industry, functional coatings are becoming more and more popular. Among them, self-healing protective coatings have good self-healing and protective functions. When the material matrix is ​​damaged, it can play a role of defense and self-repair, which can significantly extend the service life of the material and reduce maintenance costs. As people pay more attention to sustainable development and environmental protection, self-healing protective coatings are gradually developing in the direction of renewable and degradable.

[0003] Polyurethane, as a multifunctional polymer material, has excellent wear resistance, corrosion resistance, high strength, toughness and other good mechanical properties, and it also has a certain self-healing ability, which makes it have a good application prospect in the field of self-healing protective coatings. Although polyurethane has many excellent characteristics mentioned above, there are still some unresolved defects when it is used as the main component of degradable self-healing protective coatings, such as the self-healing and degradability of polyurethane itself need to be improved; and polyurethane is easy to age, and nano-filler components are often added to the coating to increase its UV resistance, but these filler components may have poor dispersion problems, which will affect the overall performance of the coating to a certain extent.

[0004] Patent CN115895428A discloses an intrinsic self-healing anti-corrosion coating and a preparation method thereof. The raw materials of the coating include polyurethane elastomer, acetone, graphene, a leveling agent and a dispersant. The coating prepared in this application can repair the same damaged area multiple times under the action of molecular bonding, has good self-healing properties, and can effectively extend the service life of the material. However, the polyurethane elastomer selected in this application is a conventional polyurethane synthesized using diphenylmethane diisocyanate and polypropylene glycol as raw materials, and its degradability is limited. In addition, graphene is prone to agglomeration and may still agglomerate under the action of a small amount of dispersant, which leads to a decrease in the overall performance of the coating.

[0005] Therefore, there is an urgent need on the market for a biodegradable self-healing protective coating with good overall performance. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention uses modified polyurethane as the main component of the coating, adds modified nano titanium dioxide, a curing agent, a leveling agent and a mixed solvent to synthesize a degradable self-healing protective coating based on nanotechnology, which has the characteristics of good UV resistance, degradability, self-healing performance and protective performance.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a biodegradable self-healing protective coating based on nanotechnology. The coating comprises the following raw materials in parts by weight: 65-80 parts of modified polyurethane, 5-15 parts of modified nano titanium dioxide, 10-20 parts of curing agent, 1-2 parts of leveling agent, and 10-20 parts of mixed solvent.

[0009] In some embodiments of the present invention, the method for preparing the modified polyurethane comprises the following steps:

[0010] (1) dehydrating lactic acid and placing it in a reaction vessel, adding stannous octoate, stirring for 4-6 hours at 0.09-0.1 MPa and 140-170° C., cooling, adding 2,2'-(1,4-phenylene)dioxazoline, stirring for 30-45 minutes at 0.09-0.1 MPa and 140-160° C., and obtaining a product for use;

[0011] (2) The product of step (1) is mixed with isophorone diisocyanate and polytetrahydrofuran diol, stannous octoate is added, and the mixture is heated to 80-90° C. under an inert atmosphere, stirred for 2-3 h, and then polyester polyol is added, stirred for 2-3 h, cooled to 55-65° C., 2-(2-propoxyethoxy)aniline is added, stirred for 1-2 h, and N-methylpyrrolidone is added, stirred, and vacuum desolventizing is performed to obtain a modified polyurethane.

[0012] Wherein, the polyester polyol is a dendritic polyester polyol.

[0013] In some embodiments of the present invention, in step (1), the mass ratio of lactic acid to 2,2'-(1,4-phenylene)bisoxazoline after dehydration is 1:(0.1-0.3).

[0014] Preferably, in the step (1), the mass ratio of lactic acid to 2,2'-(1,4-phenylene)dioxazoline after dehydration is 1:0.2.

[0015] In some embodiments of the present invention, in step (2), the mass ratio of isophorone diisocyanate, product, polyester polyol and 2-(2-propoxyethoxy)aniline is 1:(0.3-0.4):(0.06-0.1):(0.04-0.08).

[0016] Preferably, in step (2), the mass ratio of isophorone diisocyanate, the product, polyester polyol and 2-(2-propoxyethoxy)aniline is 1:0.33:0.83:0.67.

[0017] Polyurethane has the characteristics of high mechanical strength and high wear resistance, and can be used as a good protective functional material. It also has certain degradability and self-healing properties. However, its degradability is not as good as that of polymer materials such as polylactic acid, and its self-healing property may also decrease with the increase in the number of repairs. Its degradability and self-healing properties need to be improved.

[0018] On the one hand, the applicant selected lactic acid as the raw material, firstly adopted the direct melt polycondensation method and introduced 2,2'-(1,4-phenylene)dioxazoline to extend the chain of the lactic acid prepolymer to obtain a terminal hydroxyl lactic acid prepolymer (product), and then reacted the product with isophorone diisocyanate and polytetramethylene glycol to introduce the polylactic acid chain end into the modified polyurethane structure, thereby improving the degradability of the polyurethane. Furthermore, 2,2'-(1,4-phenylene)dioxazoline not only plays the role of chain extension, but also the oxazoline structure in its structure can effectively improve the heat resistance of polylactic acid, thereby improving the thermal stability of the modified polyurethane. On the other hand, the applicant introduced dendritic polyester polyol and 2-(2-propoxyethoxy)aniline to prepare a modified polyurethane, and the -NH2 in 2-(2-propoxyethoxy)aniline reacted with the -NCO group and was connected to the dendritic polyurethane molecular chain, so that the hydrogen bonds in the modified polyurethane were cross-linked, thereby making the modified polyurethane have a stable hydrogen bond network structure, thereby improving the thermal stability and self-healing properties of the modified polyurethane.

[0019] In some embodiments of the present invention, the method for preparing the modified nano titanium dioxide comprises the following steps:

[0020] Tetrabutyl titanate, hexadecanol, ammonium fluoride and lanthanum chloride are mixed, oleylamine, oleic acid and Span 80 are added, and the mixture is placed in a high gravity rotating bed after stirring. Inert gas is introduced, and the mixture is heated at 1500-2500 rpm while stirring until the mixture reaches 115-125° C., the introduction of inert gas is stopped, vacuum degassing is performed, the introduction of inert gas is continued, the mixture is heated to 290-310° C., heat preservation is performed, cooling is performed to 55-65° C., acetone is added, stirring is performed, centrifugation is performed, n-hexane and anhydrous ethanol are added, stirring is performed, washing is performed, and drying is performed to obtain modified nano titanium dioxide.

[0021] In some embodiments of the present invention, the molar ratio of tetrabutyl titanate, ammonium fluoride and lanthanum chloride is 1:(0.3-0.5):(0.2-0.4).

[0022] Preferably, the molar ratio of tetrabutyl titanate, ammonium fluoride and lanthanum chloride is 1:0.4:0.3.

[0023] Nano-titanium dioxide has good UV resistance and can be added as a nano-filler in polyurethane-based coatings. However, due to its large surface energy, nano-titanium dioxide is prone to agglomeration, resulting in poor dispersion in the coating, which in turn makes it impossible to improve the UV resistance of the coating.

[0024] On the one hand, the applicant chose to react ammonium fluoride, lanthanum chloride and tetrabutyl titanate to achieve the doping of nano-titanium dioxide with fluoride ions and lanthanum ions to prepare modified nano-titanium dioxide. Fluoride ions can enhance the hydrophobicity of the modified nano-titanium dioxide, thereby promoting the dispersibility of nano-titanium dioxide in the coating, and lanthanum ions can effectively improve the UV resistance of nano-titanium dioxide. On the other hand, the applicant selected Span 80 as a surfactant, oleic acid and oleylamine as morphology regulators, and combined the ultragravity method and the hydrothermal method to prepare the modified nano-titanium dioxide, so that the modified nano-titanium dioxide has a suitable particle size and crystallinity, so that it has good dispersibility in the coating.

[0025] In some embodiments of the present invention, the curing agent is an oxazolidine and / or imine latent curing agent.

[0026] Preferably, the curing agent is TP-830 oxazolidine latent curing agent.

[0027] In some embodiments of the present invention, the leveling agent is leveling agent PV88.

[0028] In some embodiments of the present invention, the mixed solvent is at least two of butyl acetate, xylene, and cyclohexanone.

[0029] Another aspect of the present invention further provides a method for preparing the biodegradable self-healing protective coating based on nanotechnology as described in the above technical solution, comprising the following steps:

[0030] S1, mixing the modified nano titanium dioxide and the modified polyurethane, stirring for 10-20 minutes, and obtaining a mixture for standby use;

[0031] S2. Add the leveling agent and the mixed solvent to the mixture of step S1, stir for 10-20 minutes, add the curing agent, and stir to obtain a degradable self-healing protective coating based on nanotechnology.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention uses modified polyurethane as the main component of the coating, adds modified nano titanium dioxide, a curing agent, a leveling agent and a mixed solvent to synthesize a degradable self-healing protective coating based on nanotechnology. Through the synergistic effect of the components, the degradable self-healing protective coating based on nanotechnology has good ultraviolet resistance.

[0034] (2) The present invention first selects lactic acid as a raw material, introduces 2,2'-(1,4-phenylene)dioxazoline to synthesize a terminal hydroxylactic acid prepolymer, and reacts the prepolymer with isophorone diisocyanate and polytetramethylene glycol to improve the degradability and heat resistance of the polyurethane, and further introduces dendritic polyester polyol and 2-(2-propoxyethoxy)aniline to improve the thermal stability and self-healing property of the modified polyurethane.

[0035] (3) The present invention uses ammonium fluoride, lanthanum chloride and tetrabutyl titanate as raw materials to achieve the doping of nano-titanium dioxide with fluoride ions and lanthanum ions, and combines the supergravity method and the hydrothermal method to prepare the modified nano-titanium dioxide, so that the dispersibility of the modified nano-titanium dioxide is effectively improved, and its ultraviolet resistance is further improved.

[0036] (4) The nanotechnology-based coating prepared by the present invention has the characteristics of good UV resistance, degradability, self-healing performance and protective performance, can be widely used in the field of degradable self-healing protective coatings, and has good commercial application value. DETAILED DESCRIPTION

[0037] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0038] In the following embodiments and comparative examples, except for modified polyurethane and modified nano titanium dioxide, the remaining compound monomers and related reagents used can be purchased from the market. Among them, polytetrahydrofuran diol was purchased from Hubei Yongkuo Technology Co., Ltd.; the polyester polyol is a dendritic polyester polyol, model H40P, purchased from Xiamen Aikema Chemical Co., Ltd.; the curing agent is TP-830 oxazolidine latent curing agent, purchased from Wuhan Kemik Biomedical Technology Co., Ltd.; the leveling agent PV88 was purchased from Foshan Jieke New Materials Co., Ltd.

[0039] Preparation Example 1

[0040] The synthetic method of modified polyurethane A comprises the following steps:

[0041] (1) After dehydrating the lactic acid, 30 g of the lactic acid was placed in a reaction container, 0.3 g of stannous octoate was added, and the mixture was stirred at 0.096 MPa and 160° C. for 5 h. The mixture was cooled to 150° C., 6 g of 2,2'-(1,4-phenylene)dioxazoline was added, and the mixture was stirred at 0.096 MPa and 150° C. for 40 min to obtain the product for later use;

[0042] (2) 20 g of the product of step (1) was mixed with 60 g of isophorone diisocyanate and 30 g of polytetrahydrofuran diol, 0.3 g of stannous octoate was added, and the mixture was heated to 85° C. under a nitrogen atmosphere, stirred for 2.5 h, 5 g of polyester polyol was added, stirred for 2.5 h, the temperature was lowered to 60° C., 4 g of 2-(2-propoxyethoxy)aniline was added, stirred for 1.5 h, 100 ml of N-methylpyrrolidone was added, stirred for 30 min, and vacuum desolventized to obtain modified polyurethane A.

[0043] Preparation Example 2

[0044] The specific implementation manner of modified polyurethane B is the same as that of modified polyurethane A, except that in step (1), the mass of 2,2'-(1,4-phenylene)dioxazoline is replaced with 2.4 g.

[0045] Preparation Example 3

[0046] The specific implementation method of modified polyurethane C is the same as that of modified polyurethane A, except that in step (2), the mass of the product is replaced with 16.5 g.

[0047] Preparation Example 4

[0048] The specific implementation method of modified polyurethane D is the same as that of modified polyurethane A, except that in step (2), the mass of polyester polyol is replaced by 2.4 g.

[0049] Preparation Example 5

[0050] The specific implementation manner of modified polyurethane E is the same as that of modified polyurethane A, except that in step (2), the mass of 2-(2-propoxyethoxy)aniline is replaced with 1.2 g.

[0051] Preparation Example 6

[0052] The synthesis method of modified nano titanium dioxide A comprises the following steps:

[0053] Mix 10mmol tetrabutyl titanate, 100ml hexadecanol, 4mmol ammonium fluoride and 3mmol lanthanum chloride, add 10ml oleylamine, 10ml oleic acid and 60ml Span 80, stir for 20min, place in a high gravity rotating bed, introduce nitrogen, heat with stirring at 2000rpm, heat to 120°C, stop introducing nitrogen, degas in vacuum, continue introducing nitrogen, heat to 300°C, keep warm for 1h, cool to 60°C, add 40ml acetone, stir for 5min, centrifuge, add 10ml n-hexane and 40ml anhydrous ethanol, stir for 5min, wash with anhydrous ethanol 3 times, and dry at 60°C for 24h to obtain modified nano titanium dioxide A.

[0054] Preparation Example 7

[0055] The specific implementation method of modified nano titanium dioxide B is the same as that of modified nano titanium dioxide A, except that the molar number of ammonium fluoride is replaced by 2 mmol.

[0056] Preparation Example 8

[0057] The specific implementation method of modified nano titanium dioxide C is the same as that of modified nano titanium dioxide A, except that the molar number of lanthanum chloride is replaced by 1 mmol.

[0058] Example 1

[0059] A biodegradable self-healing protective coating based on nanotechnology comprises the following raw materials by weight: 70 parts of modified polyurethane A, 10 parts of modified nano titanium dioxide A, 15 parts of TP-830 oxazolidine latent curing agent, 1.5 parts of leveling agent PV88, and 15 parts of mixed solvent.

[0060] The mixed solvent is butyl acetate and xylene in a volume ratio of 1:1.

[0061] The preparation method of the biodegradable self-healing protective coating based on nanotechnology in this embodiment comprises the following steps:

[0062] S1, mixing modified nano titanium dioxide A and modified polyurethane A, stirring for 15 minutes, and obtaining a mixture for standby use;

[0063] S2. Add the leveling agent PV88 and the mixed solvent to the mixture of step S1, stir for 15 minutes, add TP-830 oxazolidine latent curing agent, and stir for 5 minutes to obtain a degradable self-healing protective coating based on nanotechnology.

[0064] Example 2

[0065] A biodegradable self-healing protective coating based on nanotechnology comprises the following raw materials by weight: 65 parts of modified polyurethane A, 10 parts of modified nano titanium dioxide A, 10 parts of TP-830 oxazolidine latent curing agent, 1 part of leveling agent PV88, and 10 parts of mixed solvent.

[0066] The mixed solvent is butyl acetate and xylene in a volume ratio of 1:1.

[0067] The preparation method of the biodegradable self-healing protective coating based on nanotechnology in this embodiment comprises the following steps:

[0068] S1, mixing modified nano titanium dioxide A and modified polyurethane A, stirring for 10 minutes, and obtaining a mixture for standby use;

[0069] S2. Add the leveling agent PV88 and the mixed solvent to the mixture of step S1, stir for 10 minutes, add TP-830 oxazolidine latent curing agent, and stir for 5 minutes to obtain a degradable self-healing protective coating based on nanotechnology.

[0070] Example 3

[0071] A biodegradable self-healing protective coating based on nanotechnology comprises the following raw materials by weight: 80 parts of modified polyurethane A, 10 parts of modified nano titanium dioxide A, 20 parts of TP-830 oxazolidine latent curing agent, 2 parts of leveling agent PV88, and 20 parts of mixed solvent.

[0072] The mixed solvent is butyl acetate and cyclohexanone in a volume ratio of 1:1.

[0073] The preparation method of the biodegradable self-healing protective coating based on nanotechnology in this embodiment comprises the following steps:

[0074] S1, mixing modified nano titanium dioxide A and modified polyurethane A, stirring for 20 minutes, and obtaining a mixture for standby use;

[0075] S2. Add the leveling agent PV88 and the mixed solvent to the mixture of step S1, stir for 20 minutes, add TP-830 oxazolidine latent curing agent, and stir for 5 minutes to obtain a degradable self-healing protective coating based on nanotechnology.

[0076] Example 4

[0077] A biodegradable self-healing protective coating based on nanotechnology comprises the following raw materials by weight: 62 parts of modified polyurethane A, 5 parts of modified nano titanium dioxide A, 12 parts of TP-830 oxazolidine latent curing agent, 1.2 parts of leveling agent PV88 and 12 parts of mixed solvent.

[0078] The mixed solvent is the same as in Example 1.

[0079] The preparation method of the degradable self-healing protective coating based on nanotechnology in this embodiment is the same as that in Example 1.

[0080] Example 5

[0081] A biodegradable self-healing protective coating based on nanotechnology comprises the following raw materials by weight: 75 parts of modified polyurethane A, 15 parts of modified nano titanium dioxide A, 17 parts of TP-830 oxazolidine latent curing agent, 1.8 parts of leveling agent PV88, and 17 parts of mixed solvent.

[0082] The mixed solvent is the same as in Example 1.

[0083] The preparation method of the degradable self-healing protective coating based on nanotechnology in this embodiment is the same as that in Example 1.

[0084] Example 6

[0085] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polyurethane B replaces the modified polyurethane A in equal amounts.

[0086] Example 7

[0087] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polyurethane C replaces the modified polyurethane A in equal amounts.

[0088] Example 8

[0089] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polyurethane D replaces the modified polyurethane A in equal amounts.

[0090] Example 9

[0091] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polyurethane E replaces the modified polyurethane A in equal amounts.

[0092] Example 10

[0093] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified nano titanium dioxide B replaces modified nano titanium dioxide A in equal amounts.

[0094] Embodiment 11

[0095] This embodiment provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified nano titanium dioxide C replaces modified nano titanium dioxide A in equal amounts.

[0096] Comparative Example 1

[0097] This comparative example provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of polyurethane is used to replace the modified polyurethane A.

[0098] Polyurethane was purchased from Guangzhou Jingchen Plastic Chemical Co., Ltd.

[0099] Comparative Example 2

[0100] This comparative example provides a biodegradable self-healing protective coating based on nanotechnology and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of nano titanium dioxide is used to replace the modified nano titanium dioxide A.

[0101] Performance Testing

[0102] The UV resistance and self-healing properties of the biodegradable self-healing protective coatings based on nanotechnology of the above Examples 1-11 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.

[0103] The coatings obtained in the examples and comparative examples were coated on tinplate sheets with a thickness of 20 μm, and then left standing at room temperature for 24 hours to be tested for UV resistance and self-healing properties.

[0104] (1) UV resistance

[0105] The UV resistance is judged by the yellowing degree. After irradiation with a carbon rod lamp type sunlight atmospheric climate tester for 30 hours, the yellowing degree of the test piece is measured with a colorimeter. The yellowing value (Y I )express.

[0106] (2) Self-healing

[0107] The coating was scratched in the middle of one side of the tinplate sheet along the direction perpendicular to the tensile axis, and slight force was applied on both sides to make the broken parts in close contact. The self-healing efficiency was calculated at room temperature (self-healing efficiency H = impact resistance before scratching / impact resistance after scratching). The same position was scratched three times in a row to test the influence of the number of repairs on the repair effect. The impact resistance refers to the standard GB / T 1732-2020).

[0108] Table 1

[0109]

[0110]

[0111] It can be seen from the data in Table 1 that the degradable self-healing protective coating based on nanotechnology in Examples 1-5 of the present invention has good UV resistance and self-healing properties as a whole. Among them, Examples 6-9 changed the proportion of the main components in the synthesis process of modified polyurethane, so that the self-healing property of the modified polyurethane was not well improved, thereby reducing the self-healing property of the coating, but had little effect on the UV resistance, especially in Examples 8-9, the modified polyurethane failed to form a stable hydrogen bond network structure, resulting in a significant decrease in the self-healing property of the coating; Examples 10-11 changed the proportion of ammonium fluoride and lanthanum chloride added in the modified nano-titanium dioxide, so that the dispersibility and UV resistance of the modified nano-titanium dioxide decreased, thereby causing the UV resistance of the coating to decrease significantly, but had little effect on the self-healing property; Comparative Examples 1-2 respectively selected polyurethane and nano-titanium dioxide to replace modified polyurethane A and modified nano-titanium dioxide A in equal amounts, and the test found that the UV resistance and self-healing property of the degradable self-healing protective coating based on nanotechnology showed poor results.

[0112] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A biodegradable self-healing protective coating based on nanotechnology, characterized in that: The coating comprises the following raw materials by weight: 65-80 parts of modified polyurethane, 5-15 parts of modified nano titanium dioxide, 10-20 parts of curing agent, 1-2 parts of leveling agent and 10-20 parts of mixed solvent.

2. The biodegradable self-healing protective coating based on nanotechnology according to claim 1, characterized in that: The preparation method of the modified polyurethane comprises the following steps: (1) dehydrating lactic acid and placing it in a reaction vessel, adding stannous octoate, stirring for 4-6 hours at 0.09-0.1 MPa and 140-170° C., cooling, adding 2,2'-(1,4-phenylene)dioxazoline, stirring for 30-45 minutes at 0.09-0.1 MPa and 140-160° C., and obtaining a product for use; (2) The product of step (1) is mixed with isophorone diisocyanate and polytetrahydrofuran diol, stannous octoate is added, and the mixture is heated to 80-90° C. under an inert atmosphere, stirred for 2-3 h, and then polyester polyol is added, stirred for 2-3 h, cooled to 55-65° C., 2-(2-propoxyethoxy)aniline is added, stirred for 1-2 h, and N-methylpyrrolidone is added, stirred, and vacuum desolventizing is performed to obtain a modified polyurethane.

3. The biodegradable self-healing protective coating based on nanotechnology according to claim 2, characterized in that: In the step (1), the mass ratio of lactic acid to 2,2'-(1,4-phenylene)dioxazoline after dehydration is 1:(0.1-0.3).

4. The biodegradable self-healing protective coating based on nanotechnology according to claim 2, characterized in that: In the step (2), the mass ratio of isophorone diisocyanate, the product, polyester polyol and 2-(2-propoxyethoxy)aniline is 1:(0.3-0.4):(0.06-0.1):(0.04-0.08).

5. The biodegradable self-healing protective coating based on nanotechnology according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide comprises the following steps: Tetrabutyl titanate, hexadecanol, ammonium fluoride and lanthanum chloride are mixed, oleylamine, oleic acid and Span 80 are added, and the mixture is placed in a high gravity rotating bed after stirring. Inert gas is introduced, and the mixture is heated at 1500-2500 rpm while being stirred until the mixture reaches 115-125° C., the introduction of inert gas is stopped, vacuum degassing is performed, the introduction of inert gas is continued, the mixture is heated to 290-310° C., the mixture is kept warm, and the mixture is cooled to 55-65° C., acetone is added, the mixture is stirred, and the mixture is centrifuged. N-hexane and anhydrous ethanol are added, the mixture is stirred, washed, and dried to obtain modified nano titanium dioxide.

6. The biodegradable self-healing protective coating based on nanotechnology according to claim 5, characterized in that: The molar ratio of tetrabutyl titanate, ammonium fluoride and lanthanum chloride is 1:(0.3-0.5):(0.2-0.4).

7. The biodegradable self-healing protective coating based on nanotechnology according to claim 1, characterized in that: The curing agent is a latent curing agent of oxazolidine type and / or imine type.

8. The biodegradable self-healing protective coating based on nanotechnology according to claim 1, characterized in that: The leveling agent is leveling agent PV88.

9. The biodegradable self-healing protective coating based on nanotechnology according to claim 1, characterized in that: The mixed solvent is at least two of butyl acetate, xylene and cyclohexanone.

10. A method for preparing a degradable self-healing protective coating based on nanotechnology according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the modified nano titanium dioxide and the modified polyurethane, stirring for 10-20 minutes, and obtaining a mixture for standby use; S2, adding the leveling agent and the mixed solvent to the mixture of step S1, stirring for 10-20 minutes, adding the curing agent, stirring, and obtaining a degradable self-healing protective coating based on nanotechnology.